Long-term management effects on soil quality of Peach orchard (Prunus persica) - Khwairakpam Surchand Singh; S.Hazarika (Umiam : CPGS, CAU, 2013)
In India, the long-term management effects on quality characteristics of soils under annual crops have been studied by many workers.However, such studies on horticultural crops are limited and dserve attention. In fruit orchards,soil management practices such as application of fertilizers,manures,irrigation; lime etc. is concentrated mainly in drip circle and therefore, the soil in the inter-row spaces of trees is less affected by the management practices. The long-term soil management effect on quality of drip circle soils is expected to be more compared to the soils of inter-row spaces. Besides affecting spatial variability, long-term orchard management may significantly alter the overall quality of the orchard soil. Therefore, studies on management induced variability of soil quality are needed for refinement of recommended management practices to achieve soil improvement, better yields, input optimization and consequent savings. A~19 year old peach (Prunus persica) orchard of the ICAR Research Complex for NEH Region, Umiam, Meghalaya was used to study the long-term management effect on the quality of orchard soil. The entire orchard was divided into 4 blocks across the slope and each block consisted of 3 rows of plants with 15 plants in each row. Representative composite soil samples were collected from each of the blocks. Like the orchard, the adjacent undisturbed site (AUDS) also consisted of 4 blocks across the slope and representative composite soil samples were collected from each of the blocks. Altogether, 72 composite samples were collected from the experimental sites. Soil health attributes (physical, chemical and biological properties) were measured using standard protocol. The t-test was used for comparison of soil properties of different sampling sites. The variability within the orchard and between the orchard and AUDS in terms of soil quality attributes was found out by principal component analysis (PCA). The physical soil quality attributes viz. bulk density, total porosity and particle density of orchard soil did not vary significantly as compared to that of the AUDS. However, there was marked decrease(P<0.001) in maximum water holding capacity (MWHC) of the orchard soil. The chemical, biological and bio-chemical soil quality attributes of the orchard soil have undergone significant (P<0.001 to 0.01) alterations as compared to the AUDS. The pH, soil organic carbon (SOC) and hot water extractable carbonhydrate (HWEC) reduced to the extent of 0.24 and 0.26 unit, 5.9 and 7.1% and ~16 and ~17%, respectively. Application of N, P, K and S (from SSP) in the orchard soil. The concentration of microbial biomass carbon (MBC) in the orchard soils reduced (2.3 and 3.9%) significantly (P<0.001 to 0.01 as compared to AUDS. MBC showed significant positive correlation with SOC, HWEC and pH of the soils. The spatial variability of soil physical attributes except MWHC within the orchard was not apparent. However, the pH, available N, SOC, MBC, HWEC and enzyme activities in drip circle soil reduced significantly as compared to inter row space soil. Plant available P, K and S in drip circle soil also increased significantly. Rresults from PCA revealed that there was significant variability within the orchard as well as between the orchard and AUDS (as determined by ANOSM) in terms of soil quality attributes. Similarly, Soil Quality Index (SQI) value (derived from all soil quality attributes except available N, P, K and S) of the orchard was less than the AUDS. Long-term (>19 years) recommended management practices not only made significant alterations in the quality characteristics of the orchard soil but also caused spatial variability of soil attributes within the orchard. These call for modification of management practices to improve the soil quality of the orchard for sustainability of the production system.
Keywords: Peach -- Soil quality; Peach orchard -- Soil Management